Social and Technological Concerns Associated with the Usage of Ubiquitous Computing Technologies - Röcker, Carsten (Issues in information systems : IIS / International Association für Computer Information Systems, IACIS)
This paper identifies social and technological concerns, which are likely to emerge through the integration of Ubiquitous Computing technologies in future work environments. The concerns presented in this paper were collected by reviewing relevant literature from different research domains and are clustered into two groups. The first group of concerns concentrates on the violation of individual user privacy and the consequences, which arise from these privacy breaches. The second group addresses environmental and societal transformation processes caused by a large-scale penetration of future information and communication technologies into everyday life.
Keywords: Ubiquitous and Pervasive Computing; Ambient Intelligence; Human Factors; Technology Acceptance; User Requirements